Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Biro Umum Kantor Gubernur Sulawesi Barat - Inzani, Fuji; Yuliani, Yuliani (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Human resources are the driving force for the management of policies and operational activities of an organization, both profit organizations and government agencies. This makes human resources occupy an important position in the effort to achieve the planned organizational goals. Therefore, the efforts made by organizations to maintain their sustainability increasingly depend on the management of their human resources. The management of human resources can be in the form of competency development to organizational support through providing an adequate work environment and being able to drive human resources to produce high performance. The purpose of this study was to determine the effect of competence and work environment on employee performance at the General Bureau of the West Sulawesi Governor's Office. The population in this study was ASN (State Civil Apparatus) General Bureau of the West Sulawesi Governor's Office, amounting to 69 people. Because the population is relatively small, the sampling technique used is saturated sampling, where all members of the population are used as respondents. The data collection technique uses a questionnaire. The data analysis method used is multiple linear regression analysis using the SPSS program. The results showed that partially or simultaneously the variables of competence and work environment had a significant influence on employee performanceKeywords: one or more word(s) or phrase(s); that it’s important; spesific, or representative for the article